Biomechanical effects of posterior pedicle fixation techniques on the adjacent segment for the treatment of thoracolumbar burst fractures: a biomechanical analysis. Issue 13 (3rd October 2019) - Wang, Wei; Pei, Baoqing; Pei, Yuyang; Shi, Zhenpeng; Kong, Chao; Wu, Xueqing; Wu, Nan; Fan, Yubo; Lu, Shibao
Abstract: Posterior pedicle fixation technique is a common method for treating thoracolumbar burst fractures, but the effect of different fixation techniques on the postoperative spinal mechanical properties has not been clearly defined, especially on adjacent segments. A finite element model of T10-L2 with moderate T12 vertebra burst fracture was constructed to investigate biomechanical behavior of three posterior pedicle screw fixation techniques. Compared with traditional short-segment 4 pedicle screw fixation (TS-4) and intermediate long-segment 6 pedicle screw fixation (IL-6), mono-segment 4 pedicle screw fixation (MS-4) provides a safer surgical selection to prevent the secondary degeneration of adjacent segments in the long-term.